Glucocorticoid levels after exposure to predator odor and chronic psychosocial stress with dexamethasone application in rats. Issue 5 (21st May 2016) - Starcevic, Ana; Petricevic, Sasa; Radojicic, Zoran; Djulejic, Vuk; Ilankovic, Andrej; Starcevic, Branislav; Filipovic, Branislav
Abstract: This study was conducted to explore the effects of specific psychosocial paradigm on predator animal posttraumatic stress model and to test the hypothesis that psychosocially stressed rats would exibit abnormal levels of cortisol and a larger suppression of cortisol levels after the application of dexamethasone. Animals were divided in two groups: experimental and control groups. The experimental group was exposed to two types of stressors: acute immobilization stress, and combined predator stress and daily social stress with application of dexamethasone. Blood sampling was performed at three different times. We found statistically significant results after analyzing the differences between cortisol levels in different times of blood sampling in the group of animals exposed to stress with dexamethasone application. Statistical significance was found when we compared the experimental group with the control group in terms of elevated cortisol levels during blood sampling after stress paradigm exposition. Many significant disruptions in the functioning of the hypothalamic–pituitary–adrenal axis were observed, such as decrease in basal cortisol levels and enhanced dexamethasone‐induced inhibition of cortisol levels. These findings are important because their impact can translate to human individuals with posttraumatic stress disorder, which is the most important role of every animal model in research.